2006
DOI: 10.1194/jlr.m600108-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the relationship between lipoprotein lipase Asn291Ser variant and diseases

Abstract: This systematic review attempted to summarize the associations between the Asn291Ser variant in the lipoprotein lipase (LPL) gene and dyslipidemia, the risk of type 2 diabetes mellitus (T2DM), and coronary heart disease (CHD). In addition, the relationships between the Asn291-Ser variant and other metabolic diseases such as obesity and high blood pressure were also investigated in this systematic review. We systematically reviewed the literature by means of a meta-analysis. Twenty-one articles, including 19,24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 46 publications
2
29
0
1
Order By: Relevance
“…Similar to the findings of Bhanushali & Das [34] in South Indians, the N291S polymorphism was not detected in our study, although this variant has been reported to be associated with dyslipidemia, DM and coronary artery disease in a meta-analysis [35].…”
Section: Discussionsupporting
confidence: 78%
“…Similar to the findings of Bhanushali & Das [34] in South Indians, the N291S polymorphism was not detected in our study, although this variant has been reported to be associated with dyslipidemia, DM and coronary artery disease in a meta-analysis [35].…”
Section: Discussionsupporting
confidence: 78%
“…Using a stringent threshold for statistical significance but without considering biological information may falsely reject an important biological finding. Since the associations observed in the 10 genes had been reported previously in the white and black populations [3,5,6,27,[31][32][33][34][35][36], our findings were less likely to be false positive.…”
Section: Discussionmentioning
confidence: 76%
“…However, Hallman et al (10) did not find any association between the HindIII(-) allele and higher LPL activity. The associations of certain polymorphic loci in the LPL promoter, introns or exons with lipid disorders and coronary artery disease (CAD) have been reported by some groups (rs285, rs1800590, rs320, rs268, rs1801177) (6)(7)(8)(11)(12)(13)(14) but contested by other authors (15)(16)(17). To the best of our knowledge, no data on the screening of such specific polymorphisms in the Saudi population have been reported.…”
Section: Introductionmentioning
confidence: 83%